IMPROVING INDONESIAN EFL STUDENTS’ SPEAKING ABILITY THROUGH TOPIC BASED-PAIRED CONVERSATION ACTIVITY - Rahmatullah Syaripuddin (Journal of Applied Linguistics, 2022)
This research was based on the students’ problem regarding the English teaching of speaking skill. The objective of the research was to find out whether or not the implementation of topic based-paired conversation activity improves the EFL (English Foreign Language) students’ speaking ability at senior high school 3 Parepare, Indonesia. The researcher applied a quasi-experimental design, with two groups - experimental and control class. The population of the research was the eleventh-grade students at senior high school 3 Parepare. The sample of the research was taken by using total random sampling consisting of 56 students from two classes taken from the population of the eleventh-grade students. The result of the data analysis showed that the students' speaking ability improved, as evidenced by the result of probability and significant value in the post-test, where the probability value was 0.00 and the significance value was 0.05. In conclusion, teaching speaking through topic based-paired conversation activity was effective to improve the Indonesian EFL students' speaking ability. Keywords: Teaching Speaking, Speaking Ability, Topic-based paired Conversation Activity